Postfeminist neoliberalization of self-care: a critical discourse analysis of its representation in Vogue, Cosmopolitan and Elle - Martínez-Jiménez, Laura (Feminist media studies, 2023)
Encouraged by the popularization of the feminisms and the essentiality of care in the face of the increasing precarity of the living conditions, popular women's culture in the global North has been showing signs of a growing interest in self-care practices. Given this new visibility, the present work proposes a critical approach to the discursive representation of self-care from a transdisciplinary and feminist theoretical-interpretative perspective, located at the nexus of political economy and cultural studies. For this purpose, we undertake a critical discourse analysis-from a feminist perspective-of the cultural articulation of self-care in women's magazines Vogue, Cosmopolitan and Elle (Spanish editions). Among our main findings, we can highlight the hyperfeminization of self-care; the re-politicization of young women's discomfort and wellbeing in postfeminist neoliberal terms; the identification of self-care with consumption practices, especially aesthetic ones, which, in turn, are related to the financialization and indebtedness of everyday life; and the signification of self-care as utilitarian and productive, i.e., as a tool for women to constantly work on ourselves and transform ourselves to optimize ourselves in line with the feminization of the neoliberal subject and the maximization of their human/social/erotic capital.